2016
DOI: 10.2147/amep.s97658
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care echocardiography in simulation-based education and assessment

Abstract: BackgroundEmergency medicine milestones released by the Accreditation Council for Graduate Medical Education require residents to demonstrate competency in bedside ultrasound (US). The acquisition of these skills necessitates a combination of exposure to clinical pathology, hands-on US training, and feedback.ObjectivesWe describe a novel simulation-based educational and assessment tool designed to evaluate emergency medicine residents’ competency in point-of-care echocardiography for evaluation of a hypotensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…44,51 Another study utilized clinical scenarios and simulators to test a trainee's knowledge and application of knowledge, although their methodology has not been validated. 52 Further investigations are needed to validate and measure knowledge acquisition, application, and integration into clinical practice with bedside echocardiography.…”
Section: Part 2 Beyond Framework: Reviewing Current Competency Assementioning
confidence: 99%
“…44,51 Another study utilized clinical scenarios and simulators to test a trainee's knowledge and application of knowledge, although their methodology has not been validated. 52 Further investigations are needed to validate and measure knowledge acquisition, application, and integration into clinical practice with bedside echocardiography.…”
Section: Part 2 Beyond Framework: Reviewing Current Competency Assementioning
confidence: 99%
“…Studies have shown that US techniques are best taught to undergraduate students in emergency and trauma settings. ( 21 - 24 ) The major challenge is to define the best way to offer emergency and trauma US training as part of the medical undergraduate program. In June 2014, the Association for Medical Ultrasound held a forum aimed to design a roadmap for integration of US into the medical education syllabus.…”
Section: Discussionmentioning
confidence: 99%
“…Both low and high fidelity ultrasound simulation modalities are available [11]. A 1-day workshop using multi-faceted simulation based education and assessment of focused cardiac ultrasound in the evaluation of the hypotensive patient, showed improved competency in emergency medicine residents [12].…”
Section: Discussionmentioning
confidence: 99%